COMPLICATIONS OF LUNG RESECTION AND EXERCISE CAPACITY: A META-ANALYSIS - Benzo, Roberto (2007)
RATIONALE: While exercise capacity, expressed as maximal oxygen consumption (VO(2max)), has been proposed to be the best predictor of postoperative cardiopulmonary complications after surgical resection in lung cancer patients, the literature remains controversial. The purpose of this study was to use the meta-analytic approach to determine if VO(2max), expressed as either ml/kg/min or as a percentage of predicted, differed between patients who develop postoperative cardiopulmonary complications versus those that do not. METHODS: Studies were retrieved via (1) computerized literature searches, (2) cross referencing from retrieved articles, and (3) expert review of our reference list. Trials were included if they reported preoperative VO(2max) values (ml/kg/min or percentage of predicted) and had patients in which postoperative cardiopulmonary complications occurred. RESULTS: Fourteen studies representing a total of 955 men and women met our criteria for inclusion. Across all designs and categories, random-effects modeling demonstrated that patients without post operative pulmonary complications had significantly higher levels of VO(2max) in ml(.)kg(−1.)min(−1) ( mean difference = 3.0, 95% CI, 1.9 to 4.0) as well as VO(2max) as a percentage of predicted ( mean difference = 8, 95% CI, 3.3 to 12.8). CONCLUSION: After a systematic review of the literature we found that exercise capacity expressed as VO(2max), is lower in patients that develop clinically relevant complications after curative lung resection. These results are important for the practicing clinician because answers the literature controversy on the usefulness of measuring pre-operative exercise capacity and reinforce the current guidelines on decision making for lung resection.